Pairwise indirect treatment comparison of dupilumab versus other biologics in patients with uncontrolled persistent asthma. (January 2022) - Bateman, Eric D.; Khan, Asif H.; Xu, Yingxin; Guyot, Patricia; Chao, Jingdong; Kamat, Siddhesh; Rowe, Paul; Burnett, Heather; Msihid, Jerome; Weinreich, David; Pavord, Ian D.
Abstract: Background: Currently, five biologic treatment options are available for use in patients with uncontrolled persistent asthma: three interleukin (IL)-5 antagonists, which either bind to the anti-IL-5 ligand (mepolizumab, reslizumab) or to the IL-5 receptor (benralizumab); one anti-immunoglobulin E (anti-IgE) therapy (omalizumab); and one anti-IL-4/IL-13 therapy (dupilumab). To date, no comparative data from head-to-head clinical trials are available for these biologics. Objective: An indirect treatment comparison (ITC) of dupilumab versus each of the anti-IL-5 and anti-IgE therapies using the endpoints of annualized severe asthma exacerbation rates and change in pre-bronchodilator forced expiratory volume in 1 s (FEV1 ). Methods: Embase®, MEDLINE®, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for studies published between January 1, 1980 and March 25, 2019. Eligible articles included randomized controlled trials (RCTs) in patients aged ≥ 12 years with persistent/uncontrolled asthma using at least medium-to-high dose inhaled corticosteroid plus long-acting β2 -agonist with add-on biologic therapy. Bucher ITCs were performed to compare subgroups of dupilumab patients with the anti-IL-5s and anti-IgE trial populations. Results: Fourteen RCTs were included in the analyses. The matched dupilumab subgroups were associated with greater reductions in annualized severe exacerbation rates compared with benralizumab, mepolizumab, reslizumab, and omalizumab (54%, 28%, 38%, and 26% greater reduction, respectively). A greater improvement in FEV1 was also observed for dupilumab at week 12 and/or week 24/52 than for the other biologics (0.06–0.14 L). Conclusion: In this ITC, dupilumab was associated with lower severe asthma exacerbation rates and greater improvements in lung function than anti-IL-5s and omalizumab. Highlights: Dupilumab was associated with lower severe asthma exacerbation rates than anti-IL-5s and omalizumab. Dupilumab was associated with and greater improvements in lung function than anti-IL-5s and omalizumab. In the absence of any head-to-head trials, our analysis may be useful to clinicians and decision-makers considering these treatments for patients with uncontrolled persistent asthma.